Integrasi Materi IPA Dengan Nilai-Nilai Islam Untuk Pembelajaran IPA Madrasah Ibtidaiyah - Mardiana (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Education is inseparable from the learning process that is systematically arranged. Value education is not only a special program taught by several subjects, but also includes the entire learning process. Integrating values into learning is a process of directing educational exemplars aimed at instilling life values that contain noble, social, moral, and ethical values to foster students with insight. Wisdom, whole character, honorable person and fundamental ability for self, society and the State. This research aims to provide a better understanding of the importance and how to implement the integration of science material with Islamic values for science learning in Madrasah Ibtidaiyah. This research uses qualitative research methods with the type of library research or called Library Research. This research provides a deeper understanding of how the implementation of integrating science materials with Islamic values for science learning in Madrasah Ibtidaiyah. The result of this research is integrating religious values in a subject matter a teacher must be able to include religious values such as faith and devotion by linking them in the learning material to be taught.